2021
DOI: 10.3390/org2030013
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Utility of Defined Molecular Scaffolds

Abstract: A growing theme in chemistry is the joining of multiple organic molecular building blocks to create functional molecules. Diverse derivatizable structures—here termed “scaffolds” comprised of “hubs”—provide the foundation for systematic covalent organization of a rich variety of building blocks. This review encompasses 30 tri- or tetra-armed molecular hubs (e.g., triazine, lysine, arenes, dyes) that are used directly or in combination to give linear, cyclic, or branched scaffolds. Each scaffold is categorized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 346 publications
1
28
0
Order By: Relevance
“…Organic azides are widely used in synthetic chemistry as masked amine intermediates and in various other fields such as chemical biology and materials chemistry as readily connectable compounds. Particularly, the advent of click chemistry reactions such as copper-catalyzed azide–alkyne cycloaddition (CuAAC) and strain-promoted azide–alkyne cycloaddition (SPAAC) has greatly enhanced the utility of organic azides. In the course of our recent studies regarding azide chemistry, we found that a doubly sterically hindered aromatic azido group exhibited unique clickability, which enabled three and four sequential azido-type-selective triazole-forming reactions using triazido and tetraazido platform molecules (Figure A). ,, We also developed a radioisotope-free photoaffinity labeling method for the target identification of bioactive molecules using diazido probes having aromatic and aliphatic azido groups. In this method, the aromatic azido moiety serves as a photoreactive group to capture the target protein, whereas a detectable tag is introduced through the aliphatic azido group to analyze the photolabeled proteins (Figure B) .…”
Section: Introductionmentioning
confidence: 99%
“…Organic azides are widely used in synthetic chemistry as masked amine intermediates and in various other fields such as chemical biology and materials chemistry as readily connectable compounds. Particularly, the advent of click chemistry reactions such as copper-catalyzed azide–alkyne cycloaddition (CuAAC) and strain-promoted azide–alkyne cycloaddition (SPAAC) has greatly enhanced the utility of organic azides. In the course of our recent studies regarding azide chemistry, we found that a doubly sterically hindered aromatic azido group exhibited unique clickability, which enabled three and four sequential azido-type-selective triazole-forming reactions using triazido and tetraazido platform molecules (Figure A). ,, We also developed a radioisotope-free photoaffinity labeling method for the target identification of bioactive molecules using diazido probes having aromatic and aliphatic azido groups. In this method, the aromatic azido moiety serves as a photoreactive group to capture the target protein, whereas a detectable tag is introduced through the aliphatic azido group to analyze the photolabeled proteins (Figure B) .…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available amino acid building blocks with orthogonal protecting groups, 1 which usually possess a fluorenylmethoxycarbonyl (Fmoc) protecting group on their α-amine and an orthogonal protecting group (which can be removed selectively during Fmoc-SPPS) on their side-chain functional group, are efficacious for synthesizing multi-functionalized peptides, 2,3 branched peptides, [4][5][6] and cyclic peptides. [7][8][9][10][11] Particularly, orthogonally protected amino acids with sidechain-amines, such as lysine (Lys), ornithine (Orn), 2,4-diaminobutyric acid (Dab), and 2,3-diaminopropionic acid (Dap), can be elongated/functionalized individually on their α-amine or side-chain-amine using a routine coupling protocol.…”
mentioning
confidence: 99%
“…Facile methods to assemble simple modules onto platform molecules having a number of functional groups for click chemistry are of great significance for the preparation of multifunctional compounds in broad research fields such as pharmaceutical science and chemical biology. 1–4 Since click reactions have been in the construction of a vast chemical library and in the synthesis of chemical probes bearing reporter groups, various trivalent platform molecules for consecutive click reactions have been developed so far and an efficient consecutive click assembly using compact platforms is awaited (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%